PERANCANGAN PROGRAM APLIKASI PEMESANAN PADA DODO AND FRIENDS ORGANIZER - Djapri, Andrian (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
“Dodo & Friends Organizer” is a company which is engaged in a activities that prepare the wedding feast. The current “Dodo & Friends Organizer” doesn’t have a Website that can handle customer order. With Website creation is expected to improve business processes effectively and efficiently. Based journal with the title “AplikasiSistemInformasi Wedding Organizer Berbasis Web padaTelaga Sari” held a wedding is not an easy thing to do, especially in today’s world where everyone has a very solid rushing day. Many things that need to be prepared starting from The Invitation, Souvenir, Documentation, Bridal Makeup, etc.